The effect of a training program on developing some positive thinking skills among students of fine arts institutes - Hussain, Ikhlas Ali; Abdul, Khansa Abdel- Razzaq (International Journal of Psychosocial Rehabilitation, 2020)
This study gains its importance from the fact that it deals with positive thinking. The current study tries to know the effect of the training program on positive thinking among students of the Institute of Fine Arts by testing the following null hypotheses- : • There are no statistically significant differences between the experimental group’s fear scores before and after the programmed. • There are no statistically significant differences between the ranks of the experimental and control groups. To achieve the objectives of this study, two tools were used: the positive thinking scale and the program prepared according to the model prepared by the researcher. The experimental method was used to verify the hypotheses of the study. The sample consisted of (10) students who scored lower on the positive thinking scale. The sample is chosen from the Institute of Fine Arts in Baqubah. They are randomly distributed into two equal groups. The program was used according to positive thinking with the experimental group, while the control group was not exposed to such a program, and the number of counseling sessions was (12) sessions. The validity of the program is achieved by exposing it to a number of experts. In order to process data statistically, a single-sample T-test and independent samples, Man-Witny and Wilcoxen’s test are used, and the following have been discovered: • There are statistically significant differences at a significance level of 0.05 in favor of the experimental group and the program. • There are statistically significant differences at a significance level of 0.05 in the post-test in favor of the experimental group